The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/csc2.20614
|View full text |Cite
|
Sign up to set email alerts
|

Sunn hemp planting date effect on growth, biomass accumulation, and nutritive value in southeastern Wyoming

Abstract: Sustainablesuccess of the Northern High Plains (NHP) crop and livestock industry is limited by market accessibility, infertile soils, short growing seasons, and availability of high nutritive value, low-cost feed. Adoption of the tropical legume, Crotalaria juncea L. (commonly known as sunn hemp), into NHP cropping systems could improve the sustainability of the rotation by fitting into summer growing windows and being used as a hay alternative. Rainfed and irrigated studies were conducted in Lingle, WY, to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In contrast, SP concentrations in sunn hemp were greatest at the first harvest and declined with successive harvesting. These results are congruent with previous research, as sunn hemp has previously been shown to have CP concentrations >20% (Eberle & Shortnacy, 2021; Lepcha & Naumann, 2021). Sunn hemp's decline in SP was likely related to a decrease in leaf/stem ratio as the plants grew, as reported by Lepcha et al.…”
Section: Forage Mass Sampling Protocols and Nutritive Value Analysessupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, SP concentrations in sunn hemp were greatest at the first harvest and declined with successive harvesting. These results are congruent with previous research, as sunn hemp has previously been shown to have CP concentrations >20% (Eberle & Shortnacy, 2021; Lepcha & Naumann, 2021). Sunn hemp's decline in SP was likely related to a decrease in leaf/stem ratio as the plants grew, as reported by Lepcha et al.…”
Section: Forage Mass Sampling Protocols and Nutritive Value Analysessupporting
confidence: 93%
“…Additionally, we observed a 270 lb DM acre −1 decrease in the sunn hemp forage mass between Harvests 2 and 3, likely due to freezing temperatures that occurred between these harvestings. Given its origins in the tropical/subtropical climates of India (Bhandari et al., 2016), sunn hemp's poor performance as a fall forage in our study is not entirely surprising, as recent research conducted in Wyoming suggests that at more northerly latitudes it may be better suited as a summer (May–August) forage (Eberle & Shortnacy, 2021).…”
Section: Forage Mass Sampling Protocols and Nutritive Value Analysesmentioning
confidence: 58%
“…An initial 30-day slow growth rate, as reported in other studies, seems typical for the crop regardless of growing environment (Eberle & Shortnacy, 2021;Schomberg et al, 2007;Srisaikham & Lounglawan, 2018). Under irrigated conditions, sunn hemp should be closely monitored during establishment as it is highly sensitive to excess water that could delay growth (Eberle & Shortnacy, 2021). This might allow producers to use irrigation water on more sensitive crops.…”
Section: Sunn Hemp Biomass Accumulationmentioning
confidence: 72%
“…While some research has been done on the management of sunn hemp specifically in terms of planting and harvest date, further research on sunn hemp production in the NHP is needed (Lepcha et al., 2019; Eberle & Shortnacy, 2021; Srisaikham & Lounglawan, 2018). Here we test the hypothesis that an optimal initial harvest time and cutting height will maximize the total season biomass and nutrient accumulation of the cumulative initial and regrowth sunn hemp biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available plant fibers, hemp is known for its lightweight and better mechanical strength leading to an impressive strength-to-weight ratio [ 7 , 8 ]. Its quicker growth and resilience to extreme weather add value to production and promotion [ 9 , 10 ]. However, plant-based materials suffer from the disadvantages such as their hydrophilicity which enable them to readily absorb moisture compromising their mechanical and other physical properties and resulting in reduced longevity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%